Recurrent giant abdominal cerebrospinal fluid pseudo cyst: A case report and review of literature - Ram Jeewan Singh; Bijay Kumar Suman; Shreyas Dudhani; Amit Kumar Sinha; Bindey Kumar (Elsevier, 2022)
Cerebrospinal fluid pseudo cyst is a rare complication of ventriculoperitoneal shunt procedure for hydrocephalus. It is a collection of fluid that accumulate around the tip of the distal catheter and surrounded by a wall of fibrous tissue lacking a true epithelium. There is no exact etiology for this entity. It is associated with high recurrence rate. We are reporting one such case of recurrent cerebrospinal fluid pseudo cyst which was managed by initial exteriorization of abdominal end of shunt followed by excision of the cyst and revision of abdominal end of ventriculoperitoneal shunt.